(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2025)
This paper examines some paradoxes present in environmentally engaged art practices, language, and storytelling, exploring possible bifurcations capable of challenging current hegemonic worldviews. Using the concept of compostingwithcare, we critique the anthropocentrism inherent in narratives incorporated into art discourses such as sustainability and, by examining transdisciplinary intersections between the body and techne in art, offer alternatives. With a focus in biotechno and environmental art, the paper interrogates whether art can move beyond aura and denunciation and suggests that to enable alternative visions of the Anthropocene and inspire systemic change, art needs to incorporate ethics and morethanhuman perspectives into its practice by engaging with local communities and fostering a sense of care, responsibility, and reciprocity. Going beyond aesthetic gestures of environmentalism, artistic praxis must foster an intersectional relationality that cares for epistemological diversity; for example, an artistic praxis model with a long history in the translocal artistic networks of Latin America. Contrary to “sustainability”, this model seeks a plethora of bifurcations to bring about a pluralistic paradigm change. By situating artworks as points of intersection between actors in a mesh, artistic praxis may be understood as negentropic in its generation of multiscalar diversity and cobecomings and thus curative of the trappings of algorithmic governance. We argue for an art that cares for relations between different actors: human and morethanhuman, that cares for difference and that generates the frictions needed to effect change. An art that cares and also understands the importance of letting things be without human intervention.